Civil Nationalism through Criminal Legislation in Iran (Study of the Process of Activities Leading to the Legislation of Criminal Laws Supporting Ethnic-Religious Identities in Iran) - Hossein Mirmohammad Sadeghi; Alireza Gharaghani (پژوهشهای حقوقی)
Civil nationalism is a type of "belief in the nation" in Which, despite the existence of diversity and fragmentation in cultural, ethnic, and religious components, is defined mainly based on the equal right of citizenship and the will to live together. In Iran, since the constitutional revolution until now, there has been an effort to prioritize the idea of civil nationalism over competing types, namely cultural and ethnic nationalism, in which emphasis is placed on language, religion, history, or common heritage and the revival of the great civilization of the past. Although in most of this period, the cultural approach has prevailed, the growth rate of its civil type from the context of criminal legislations increased from the eighties and reached its peak in the late nineties when three bills were presented in the 10th and 11th parliaments. These bills include the bill of "Insulting the legal religions, culture, language and legitimate customs of ethnic groups"/ the bill of "Adding two articles to the Islamic Penal Code/ and the bill of "Repressing of Racial Discrimination, Ethnic and Religious Hatred" which Finally, parts of the content of all three bills were merged and Enacted in the form of “Repeated” Articles 499 and 500 of the Taziraat section of the Islamic Penal Code. In this effort in the nineties, the demand of the people on the one hand, and the response of the elected representatives of the nation in the parliament, especially the representatives of ethnic and religious identities in the minority, played a prominent role. However, these efforts are still incomplete and there are serious gaps, especially in relation to technical burden of proof and the scope of inclusion.